EXPLORING KEY FACTORS INFLUENCING THE PLACEMENT OF OPEN SPACES IN RESIDENTIAL COMPLEXES TO ENHANCE QUALITY OF LIFE - Khosrowjerdi, Behrooz; Noshadi, Mahnaz (Journal of Architecture&ENVIRONMENT, 2025)
Open spaces in residential complexes function as critical social infrastructure, yet evidence-based frameworks for their strategic placement remain underdeveloped. This study identifies and prioritizes twelve key factors influencing open space location decisions in high-density residential contexts using the Fuzzy Delphi Method. Grounded in Place Attachment Theory, Attention Restoration Theory, and WHO Quality of Life frameworks, a multidisciplinary expert panel evaluated the factors through linguistic scales converted to triangular fuzzy numbers. Defuzzification procedures (acceptance criteria: A ≥ 0.5, d < 0.2) revealed a clear hierarchical structure. Social Interactions emerged as the primary driver (A = 0.733), validating open spaces as social infrastructure rather than merely physical amenities. Visual Quality (A = 0.703) and Long-term Sustainability (A = 0.690) ranked second and third, emphasizing aesthetic engagement and ethical imperatives. Supporting factors, including Privacy, Activities, Security, Spatial Continuity, Accessibility, Environmental Comfort, Multi-functionality, Cultural Context, and Permeability, demonstrated moderate importance as enabling conditions. The findings provide empirically validated design frameworks, challenging conventional planning paradigms that prioritize technical standards over human-centered outcomes.